Oracle database 11g : a beginner's guide - Abramson, Ian (Oracle Press/McGraw Hill, 2009)
"Master Oracle Database 11g fundamentals quickly and easily. Using self-paced tutorials, this book covers core database essentials, the role of the administrator, high availability, and large database features. Oracle Database 11g: A Beginner's Guide walks you, step by step, through database setup, administration, programming, backup, and recovery. In-depth introductions to SQL and PL/SQL are included"--Resource